Quantum-Dot Cellular Automata-Based Full Adder Design: Comprehensive Review and Performance Comparison. (10th January 2023) - Joy, Upal Barua; Chakraborty, Shourov; Islam, Sharnali; Zaman, Hasan U.; Hasan, Mehedi
Abstract : Being one of the promising techniques for future computing systems, quantum-dot cellular automata (QCA)-based circuit design has gained massive interest among researchers due to which numerous QCA-based full adder (FA) circuits have been designed. Due to numerous QCA FA circuits available in the existing literature, researchers find it difficult to invest the time to search, implement, simulate, and analyze QCA FAs to find the best-suited design according to their needs. Existing review articles do not present a complete overview and performance comparison of QCA FAs. Also, the existing articles do not include quite a number of QCA FA designs in the literature review. As a result, a detailed review including all possible QCA FAs becomes essential. Therefore, rather than going for a new QCA FA design, this research aims to aid researchers by providing an extensive literature review and comprehensive study on existing QCA FAs. A total of 47 QCA FAs have been considered for analysis. The QCA FA implementation method and performance parameters are summarized in a tabular manner to provide a quick overview and comparison of the QCA FAs.